'Intern Llife': a longitudinal study of burnout, empathy, and coping strategies used by French GPs in training. Issue 2 (2017) - Galam, Eric; Soupault, Camille Vauloup; Bunge, Lucie; Vaure, Celine Buffel du; Boujut, Emilie; Jaury, Philippe
No abstract available